Implementing FPGA based PID-controller for Extrusion to Reduce Raw Material Wastage - Hussain, Samreen; Ismail, Muhammad; Waqar, Adnan; Amjad, Muhammad Ali; Iqbal, Muhammad Mubeen; Shaur, Muhammad; Arshad, Rimsha (2018 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2018)
In this paper SIMULINK and Xilinx System Generator is deployed to develop a digital PID-controller, which can provide efficient temperature control for industrial extrusion process. The modelled controller was simulated to determine the effectiveness of PID-control algorithm; however, the PID tuning is done manually. After tuning for best response, the netlist for PID-controller is generated and then implemented using VHDL to develop prototype on FPGA. The experimental implementation and testing were carried out on an industrial extrusion process plant. The prototype plant was also developed as a test bench. This paper presents a low cost solution for implementing PID-control in automation processes to reduce the wastage of raw material as in burning and decolourization due to delay in temperature control. Using FPGA as processing chip, the control process gets speed, accuracy, reliability and re-configurability. The quality of product was compared under three conditions namely Without PID, Un-tuned PID and Tuned PID. The burning effect was maximum without PID, slightly better with Un-tuned PID and minimum with tuned PID hence saving the wastage of raw material and overall production cost.